Tradisi Pembacaan Delapan Surah Pilihan Oleh Santri Tahfiz: (Studi Living Qur’an di Pondok Pesantren Mahasiswa Al-Jihad Surabaya) - Aljabbar, Muhammad Muslich; Wildah Nurul Islami (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research examines the phenomenon of Living Qur’an in Pondok Pesantren Mahasiswa Al-Jihad Surabaya which has been going on since 2015 and is manifested through the tradition of reading eight selected surahs every last Thursday of the month. The surahs read include al-Kahfi, al-Sajdah, Yasin, al-Dukhan, al-Waqi‘ah, al-Mulk, al-Insan, and al-Buruj. This tradition is only followed by tahfiz students and has been going on for generations without an explicit explanation of its benefits from the teacher. This study aims to examine the procession of tradition implementation and understand its meaning for tahfiz teachers, tahfiz administrators, and tahfiz students. The method used is descriptive-qualitative with Alfred Schutz's phenomenological approach. The results showed that the tradition procession consisted of five stages. First, the recitation of the kalam qadim prayer. Second, the recitation of tawasul. Third, the recitation of eight selected surahs alternately by tahfiz students. Fourth, the reading of tahlil, mauizah hasanah, and prayer together. Fifth, eating together. In terms of subjective and objective meanings, this tradition is seen as special, sacred, and a distinctive identity of tahfiz Al-Jihad students. The motives behind this tradition, both in terms of because of motive and in order to motive, include spiritual needs, obedience to the teacher, the obligation to follow the rules of the pesantren, a means to murajaah memorisation of the Qur'an, and the hope of getting blessings from each surah read and becoming a better person in the future.